Anlotinib plus etoposide increases survival in patients with small-cell lung cancer after chemoradiotherapy. Issue 4 (December 2022) - Gao, Lizhen; Wang, Junqing; Chen, Junlin; Zhang, Xuelin; Zhang, Manman; Wang, Suling; Zhao, Chen
Abstract: Objectives: Small-cell lung cancer is a recalcitrant subtype of lung cancer with rapid progression and high metastasis. This study compared the efficacy of anlotinib plus etoposide with etoposide alone for extensive-stage small-cell lung cancer after chemoradiotherapy. Methods: A total of 100 patients who had standard first-line chemoradiotherapy were enrolled, 50 of whom were treated with anlotinib plus etoposide and the other 50 with etoposide. The therapeutic efficacy and treatment-related adverse events were respectively evaluated using the Response Evaluation Criteria in Solid Tumors version 1.0 and the Common Terminology Criteria for Adverse Events version 4.0. The progression-free survival and overall survival of patients were analyzed using the Kaplan-Meier method. The univariate and multivariate prognostic analyses were conducted using the Cox's proportional risk regression model. Results: The median of progression-free survival in patients treated with anlotinib plus etoposide was 7 months, compared to 5.5 months for patients treated with etoposide. The 1- and 2-year survival rates of patients treated with anlotinib plus etoposide were 70% (35/50) and 20% (10/50), compared with 50% (25/50) and 8% (4/50) for patients treated with etoposide. The incidence of neutropenia was higher in patients treated with anlotinib plus etoposide than in those treated with etoposide alone. Smoking status and tumor-lymph node-metastasis stage were independent risk factors while the treatment of anlotinib plus etoposide was the independent protective factor for the relapse of the cancer. Conclusion: Anlotinib plus etoposide was more effective in extending progression-free survival and overall survival in extensive-stage small-cell lung cancer patients compared to etoposide alone.